2021
DOI: 10.1126/sciadv.abi4379
|View full text |Cite
|
Sign up to set email alerts
|

Exendin-4 gene modification and microscaffold encapsulation promote self-persistence and antidiabetic activity of MSCs

Abstract: Mesenchymal stem cell (MSC)-based therapy to combat diabetic-associated metabolic disorders is hindered by impoverished cell survival and limited therapeutic effects under high glucose stress. Here, we genetically engineered MSCs with Exendin-4 (MSC-Ex-4), a glucagon-like peptide-1 (GLP-1) analog, and demonstrated their boosted cellular functions and antidiabetic efficacy in the type 2 diabetes mellitus (T2DM) mouse model. Mechanistically, MSC-Ex-4 achieved self-augmentation and improved survival under high gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…The Exendin-4 secreted by MSC-Ex-4 improved MSC survival under high glucose stress via autocrine activation of the GLP-1R-mediated AMPK signaling pathway, as well as suppressed senescence and apoptosis of pancreatic β -cells through endocrine effects. We also showed that the amplified secretion of bioactive factors (e.g., IGFBP2 and APOM) of MSC-Ex-4 paracrinely augments insulin sensitivity and decreases lipid accumulation in hepatocytes through PI3K-AKT activation [ 30 ]. Indisputably, the functional proteins secreted by genetically modified MSCs may be useful to mitigate NASH and metabolic-associated fatty liver disease (MAFLD) concomitantly, concerning that diabetes is intimately associated with these complications.…”
Section: Preclinical Studies Of Mscs For T2dm Treatmentmentioning
confidence: 99%
“…The Exendin-4 secreted by MSC-Ex-4 improved MSC survival under high glucose stress via autocrine activation of the GLP-1R-mediated AMPK signaling pathway, as well as suppressed senescence and apoptosis of pancreatic β -cells through endocrine effects. We also showed that the amplified secretion of bioactive factors (e.g., IGFBP2 and APOM) of MSC-Ex-4 paracrinely augments insulin sensitivity and decreases lipid accumulation in hepatocytes through PI3K-AKT activation [ 30 ]. Indisputably, the functional proteins secreted by genetically modified MSCs may be useful to mitigate NASH and metabolic-associated fatty liver disease (MAFLD) concomitantly, concerning that diabetes is intimately associated with these complications.…”
Section: Preclinical Studies Of Mscs For T2dm Treatmentmentioning
confidence: 99%
“…Their main enzymatic activities involved acetylation, desuccinylation, deproprionylation, demalonylation, demyristoylation, and mono-ADP-ribosylation of both histone and non-histone proteins. The modulation of the activities of these enzymes may open new therapeutic alternatives to treat the pathologies involving SIRTs, including DR. For instance, treatment withmEX-4 increases the expression of SIRT1 and SIRT3, resulting in retinal cell protection from ROS [ 75 , 76 ]. SIRT1 activators, such as the natural product resveratrol and the synthetic STACs, increase mitochondrial function, insulin sensitivity, and cell survival through the stimulation of SIRT1-mediated deacetylation of p53.…”
Section: Discussionmentioning
confidence: 99%
“…In this animal model, diabetes was associated with elevated ROS levels causing retinal cells death, along with reduced SIRT1 concentrations. Notably, EX-4 administration reduced the formation of H 2 O 2 -induced ROS and increased SIRT1 levels, ultimately leading to a decrease of retinal cell death [ 75 ].…”
Section: Sirtuins and Diabetic Retinopathymentioning
confidence: 99%
“…Stem cells are defined as undifferentiated cells by the ability to self-renew, differentiate into different types of cells, proliferate and regenerate tissues. Stem cells have been widely used in preclinical and clinical studies of regenerative medicine, such as osteoarthritis (OA) ( Xing et al, 2020a ; Xing et al, 2020b ), cartilage defect ( Ning et al, 2019 ; Li et al, 2021 ), diabetes ( Zhang et al, 2021 ), heart injury ( Tang et al, 2018 ) and so on. However, there is still a huge challenge in the widespread application of stem cells in regenerative therapy.…”
Section: Introductionmentioning
confidence: 99%